IMPLEMENTATION OF ROCK MINING POLICY AFTER LAW NUMBER 23 OF 2014 (STUDY OF ROCK MINING PERMIT IN SUBANG DISTRICT WEST JAVA PROVINCE) - Suyasa, Gede; Hamdi, Muchlis; Teguh, Prio; Megandaru, Megandaru (Badan Pemeriksa Keuangan Republik Indonesia, 2019)
The purpose of this study is to analyze and study the process of rock mining permit including the effectiveness and benefit from policy implementation related to the abolition of the authority of regency/city government in the rock mining activity after the enactment of Law Number 23 of 2014 in Subang Regency. The method used in this study is a qualitative method by interviewing parties related and literature review. The results of the study indicate that there are differences in the duration of the permit for rock mining due to differences in the process of issuing rock mining permits before and after the authority of the management of rock mining by the province. The social impact of the transfer of authority over the management of rock mining does not affect the surrounding community. This is due to the coordination and written agreements between the entrepreneur and the community related to the social responsibility management of the entrepreneur to the community.